Sensibilidade dolorosa à palpação em pacientes con disfunção temporomandibularr crônica - Franco, Ana Lúcia [UNESP]; Oliveira, Caroline Borges de [UNESP]; Fernandes, Giovana [UNESP]; Castanharo, Sabrina Maria [UNESP]; Gonçalves, Daniela Aparecida de Godoi [UNESP]; Camparis, Cinara Maria [UNESP] (My University, 2011)
The cephalalgias are frequently associated with the temporomandibular disorders being common to find an increase of pain sensitivity in these patients. Thus, the objective of present study was to assess the sensitivity to palpation in patients presenting with chronic temporomandibular disorders comparing two groups one with headache and other without it, respectively. The temporomandibular disorders and the primary cephalalgias were diagnosed according the Diagnostic Criteria for the Research of Temporomandibular Disorders and by a questionnaire based on the International Classification of the Cephalalgias (2004). Location, assessment and grouping of muscular and articular areas for palpation were carried out according to the Diagnostic Criteria for above mentioned disorders, considering bilaterally the masseter muscle, the temporalis muscle, the cervical region and the temporomandibular joint. Sample included 213 (88.0 %) of women and 29 (12.0 %) men with a mean age of 37.41 years. The mean of number of zones positive to palpation in the groups without headaches, tension headache, migraine and daily chronic headache were: 12.43, 14.38, 15.21 and 15.62 (p= 0.107) (min 2 max 22). The areas of temporalis muscle showed significant differences among groups (p= 0.007). The number of painful points was not statistically different among groups and only in the temporalis muscle there were differences with statistical significant to palpation.
Painful sensitivity to palpation in patients presenting with chronic temporomandibular dysfunction
Keywords: Facial pain; Headaches; Temporomandibular joint